THE RELATIONSHIP OF TYPES OF GADGETS USED TO HEALTH DISORDERS EXPERIENCED DURING ONLINE LECTURE - Ni Kadek Indria Mandala Putri; Luh Putu Ruliati; Yuliana Radja Riwu (Journal of Health and Behavioral Science, 2022)
The use of gadgets during online lectures brings various impacts in the form of health problems both in mental and physical aspects. Health problems experienced during online lectures appear in various forms of complaints including stress and eye fatigue. The research aims to see the relationship between the type of gadget with stress and eye fatigue and to see the difference in stress levels, and eye fatigue based on the type of gadget used by students of the Public Health Science (PHS), Undana Kupang Study Program. The results showed that there was no relationship between the type of gadget used with stress in PHS Undana Study Program students with p-value > (0.05). There is a significant relationship and influence on the type of gadget used on eye fatigue. The results of the different tests showed that there was no significant difference in stress levels based on the type of gadget used, and there was a significant difference in eye fatigue based on the type of gadget used. This study shows that maintaining optimal visibility of gadgets, especially for smartphone users, and stress management needs to be considered for comfort during online lectures. Keywords: (Types of gadgets, Stress, and eye fatigue) Abstrak. Penggunaan gadget selama perkuliahan daring membawa berbagai dampak berupa gangguan kesehatan baik dalam aspek mental maupun fisik. Gangguan kesehatan yang dialami selama perkuliahan daring muncul dalam berbagai bentuk keluhan diantaranya stres dan kelelahan mata. Penelitian bertujuan untuk melihat hubungan jenis gadget dengan stress dan kelelahan mata serta melihat perbedaan tingkat stress dan kelelahan mata berdasarkan jenis gadget yang digunakan mahasiswa Prodi IKM Undana Kupang. Hasil penelitian menunjukan bahwa tidak ada hubungan antara jenis gadget yang digunakan dengan stres pada mahasiswa Prodi IKM Undana dengan p-value > α (0,05). Terdapat hubungan dan pengaruh yang signifikan pada jenis gadget yang digunakan terhadap kelelahan mata. Hasil uji beda menunjukkan tidak ada perbedaan yang signifikan pada tingkat stress berdasarkan jenis gadget yang digunakan dan ada perbedaan yang signifikan pada tingkat kelelahan mata berdasarkan jenis gadget yang digunakan. Penelitian ini menunjukkan menjaga jarak pandang yang optimal terhadap gadget terutama untuk pengguna smartphone serta manajemen stress perlu diperhatikan demi kenyamanan selama menjalani perkuliahan daring. Keywords: (Jenis gadget, Stress dan Kelelahan Mata)